Escalation to weekly dosing recaptures response in adalimumab‐treated patients with moderately to severely active ulcerative colitis. Issue 5 (15th July 2014) - Wolf, D.; D'Haens, G.; Sandborn, W. J.; Colombel, J.‐F.; Van Assche, G.; Robinson, A. M.; Lazar, A.; Zhou, Q.; Petersson, J.; Thakkar, R. B.
Summary Background Patients with moderately to severely active ulcerative colitis occasionally do not respond to or lose initial response to maintenance dosing of anti‐TNF therapy. Aim To report the efficacy of escalation from every other week (EOW) to weekly adalimumab dosing in patients from the clinical trial ULTRA 2 (NCT00408629), by week 8 response (i.e. response after adalimumab induction therapy). Methods Week 52 remission, response, and mucosal healing rates were assessed in ULTRA 2 adalimumab‐randomised patients who escalated to weekly dosing. Patients were stratified by week 8 response per partial Mayo score. Kaplan–Meier and logistic regression analyses estimated time to weekly dosing and defined predictors of escalation to weekly dosing, respectively. Adverse events were reported for patients receiving open‐label adalimumab. Results The rate of escalation to weekly dosing was 16.3% (20/123) for week 8 responders and 38.4% (48/125) for week 8 nonresponders. Week 52 remission, response and mucosal healing rates with weekly dosing were 20%, 45%, and 45% for week 8 responders and 2.1%, 25% and 29.2% for nonresponders, respectively (NRI). The median time to weekly dosing was 288 days for week 8 nonresponders and not estimable for responders. Prior anti‐TNF use was a significant predictor of escalation to weekly dosing. Treatment‐emergent adverse event rates were similar for patients receiving open‐label EOW or weekly adalimumab. Conclusions Escalation to weekly adalimumab dosing demonstrated clinical benefits for patients who lost response to therapy and may be beneficial for patients not initially responding to induction therapy. No new safety risks were identified with weekly dosing.